Development of a novel postnatal neurobehavioral scale for evaluation of common marmoset monkeys. Issue 4 (12th February 2015) - Braun, Katarina; Schultz‐Darken, Nancy; Schneider, Mary; Moore, Colleen F.; Emborg, Marina E.
Abstract : Common marmoset ( Callithrix jacchus ) monkeys when compared to rhesus macaques ( Macaca mullatta ) present several advantages for disease modeling, especially transgenic initiatives, as they commonly give birth to twins, which increases sample size, have accelerated development and a shorter life span that facilitates the analysis of the onset of age‐related diseases. Yet, no tools are currently available to assess marmoset neurodevelopment during the initial first month of life. Here we report the creation of a novel Primate Postnatal Neurobehavioral Assessment Scale for marmoset monkeys (PPNAS‐M) that was based on currently available scales for human and rhesus monkeys. Twenty‐four healthy marmoset infants (12 females, 12 males) from 12 families were evaluated. The infant assessments involved 10‐minute testing administered at 15 and 30 days after birth. The PPNAS‐M consists of 41 noninvasive tests grouped into 5 testing categories: visual orienting, auditory and spatial orienting, motor responses, righting and body strength, and temperament tests. Testing at these two ages did not affect the overall health of the infants, suggesting that the PPNAS‐M is a non‐invasive testing tool. Significant maturation was demonstrated by increased scores in each of the five testing categories from postnatal day 15 to 30, with developmental patterns unique to marmosets. Principal component analysis defined 4 item groups (Orientation, State Control, Motor Maturity and Sensory Sensitivity) with 5 variables each. Orientation and State Control factors were highly similar to each other at both ages and correlated highly with previous item groupings used with rhesus macaques. Our results indicate that the PPNAS‐M is a useful assessment tool for detecting neuromotor, attention, and temperament status of infant marmosets and that it is sensitive to developmental effects. Further studies to validate the PPNAS‐M for the assessment of normal development versus early effects of developmental perturbations associated to prenatal exposures and transgenesis are warranted. Am. J. Primatol. 77:401–417, 2015. © 2015 Wiley Periodicals, Inc.